Inhibition of rice germination by ustiloxin A involves alteration in carbon metabolism and amino acid utilization - Fu, Xiaoxiang; Jin, Yu; Paul, Matthew J.; Yuan, Minxuan; Liang, Xingwei; Cui, Ruqiang; Huang, Yingjin; Peng, Wenwen; Liang, Xiaogui (Frontiers in Plant Science, 2023)
Ustiloxins are the main mycotoxin in rice false smut, a devastating disease caused by Ustilaginoidea virens. A typical phytotoxicity of ustiloxins is strong inhibition of seed germination, but the physiological mechanism is not clear. Here, we show that the inhibition of rice germination by ustiloxin A (UA) is dose-dependent. The sugar availability in UA-treated embryo was lower while the starch residue in endosperm was higher. The transcripts and metabolites responsive to typical UA treatment were investigated. The expression of several SWEET genes responsible for sugar transport in embryo was down-regulated by UA. Glycolysis and pentose phosphate processes in embryo were transcriptionally repressed. Most of the amino acids detected in endosperm and embryo were variously decreased. Ribosomal RNAs for growth was inhibited while secondary metabolites salicylic acid was also decreased under UA. Hence, we propose that the inhibition of seed germination by UA involves the block of sugar transport from endosperm to embryo, leading to altered carbon metabolism and amino acids utilization in rice plants. Our analysis provides a framework for understanding of the molecular mechanisms of ustiloxins on rice growth and in pathogen infection.